PRODUCTIVITY AND ECONOMICS OF POTATO UNDER IRRIGATED CONDITIONS IN WESTERN UTTAR PRADESH - Singh, Name; Singh, Harbir (Potato Journal, 2013)
Field studies were carried out during two consecutive years i.e. 1999 and 2000 on lighttextured (typic-Ustocrept) soils at A.S. College, Lakhaoti Bulandshahar to study the effect of variety, plant population and fertility levels on the productivity and economics of potato under irrigated conditions in western Uttar Pradesh. The study revealed that potato cv. Kufri Anand gave maximum yield (320 q/ha), tuber numbers (667 thousand/ha), gross return (Rs. 54,400 /ha), net return (Rs. 19,809 /ha) and B:C ratio of 1.57 with high fertility levels (270:120:150 Kg N, P2O5 and K2O /ha) applied through inorganic fertilizers integrated with farm yard manure in 2:1 ratio on N basis. The plant population of 66,666 plants /ha gave higher net return (Rs. 17,933 /ha) and B:C ratio (1.59) closely followed by plant population of 83,333 plants /ha at 60 x 20 cm spacing which gave net return of Rs. 16,981 /ha and B:C ratio of 1.50.